SURVEI FAKTOR KESULITAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS RENDAH SEKOLAH DASAR - Wynne Stevania Iryani; Syarif Sumantri; Linda Zakiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is key in facing the changes of time, yet the issue of illiteracy still prevails in Indonesia. Bahasa Indonesia plays a crucial role in education, especially in developing students' writing skills in elementary school. This research employs a survey method to identify the factors contributing to low writing proficiency among elementary school students. The findings indicate that intellectual, psychological, and environmental factors play significant roles. Holistic and inclusive teaching strategies, along with increased support for educators, are necessary to enhance students' writing abilities at the elementary school level.